PP150 Rapid Analgesia For Prehospital Hip Disruption: A Feasibility Study. (2017) - Bulger, Jenna; Brown, Alan; Evans, Bridie; Fegan, Greg; Ford, Simon; Guy, Katy; Jones, Sian; Keen, Leigh; Khanom, Ashrafunnesa; Pallister, Ian; Rees, Nigel; Russell, Ian; et al.
Abstract : INTRODUCTION: Adequate pain relief at the scene of injury and during transport to hospital is a major challenge in all acute traumas, especially for those with hip fractures, whose injuries are difficult to immobilize and long-term outcomes may be adversely affected by administration of opiate analgesics. Fascia Iliaca Compartment Block (FICB) is a procedure routinely undertaken by clinicians in emergency departments for hip fracture patients, but use by paramedics at the scene of emergency calls, is not yet evaluated (1). METHODS: We undertook a randomized controlled feasibility trial using novel audited scratchcard randomization to allocate eligible patients to FICB or usual care. Paramedics are recruited and trained to assess patients for hip fracture and carry out FICB. We will follow up patients to assess accuracy of paramedic diagnosis, acceptability to patients and paramedics, compliance of paramedics and also measures of pain, side effects, time in hospital and quality of life in order to plan a full trial if appropriate. The primary outcome measure is health related quality of life, measured using Short Form (SF)-12 at 1 and 6 months. Interviews and focus groups will be used to understand acceptability of FICB to patients and paramedics. This study was funded by Health and Care Research Wales (1003). RESULTS: We have developed: paramedic pathway to assess patients for hip fracture and FICB paramedic training package, delivered by Consultant Anaesthetist randomization scratchcards. To date we have recruited nineteen paramedics; ten are fully trained and recruiting patients, the remainder are being trained. Fifty-four patients have been randomized and thirty-five have consented to follow-up. Thirteen 1-month and five 6-month follow-up questionnaires have been received. CONCLUSIONS: This study will enable us to recommend whether to undertake a definitive multi-centre randomized controlled trial of FICB by paramedics for hip fracture to determine if the procedure is effective for patients and worthwhile for the National Health Service.